2016
DOI: 10.2139/ssrn.2885974
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mandatory Paid Sick Leave Laws on Labor Market Outcomes, Health Care Utilization, and Health Behaviors.

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The RRs for the change in rates of occupational injuries and illnesses varied greatly among the detailed service occupations affected by the law, which may suggest that the impact of paid sick leave on occupational injuries and illnesses is differential with respect to the occupation. These findings are consistent with previous research which has shown occupational injuries and illnesses to be associated with a wide range of health outcomes including occupational injuries …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The RRs for the change in rates of occupational injuries and illnesses varied greatly among the detailed service occupations affected by the law, which may suggest that the impact of paid sick leave on occupational injuries and illnesses is differential with respect to the occupation. These findings are consistent with previous research which has shown occupational injuries and illnesses to be associated with a wide range of health outcomes including occupational injuries …”
Section: Discussionsupporting
confidence: 93%
“…Previous research has demonstrated an association between paid sick leave and a number of health indicators. In nationally representative surveys, workers with paid sick leave have been found to have a lower risk of all‐cause mortality, fewer emergency department visits, and lower prevalence of psychological distress and self‐rated fair or poor health . The study examining all‐cause mortality found that the risk of mortality was lowest for heart disease and unintentional injuries .…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the first paid sick leave mandates found mixed evidence on whether mandating access affects leave-taking behavior (Stearns and White, 2018;Maclean, Pichler and Ziebarth, 2020) or employment and earnings (Callison and Pesko (2016); Ahn and Yelowitz (2016); Pichler and Ziebarth (2020); Al-Sabah and Ouimet (2022)). Other studies found evidence that mandating paid sick leave improved health (Stearns and White, 2018;Pichler and Ziebarth, 2017) and increased health care utilization (DeRigne, Stoddard-Dare and Quinn, 2016;Jeung, Lee and Gimm, 2021).…”
Section: Introductionmentioning
confidence: 99%